2016
DOI: 10.1007/s00209-016-1694-x
|View full text |Cite
|
Sign up to set email alerts
|

Generic boundary behaviour of Taylor series in Hardy and Bergman spaces

Abstract: It is known that, generically, Taylor series of functions holomorphic in the unit disc turn out to be universal series outside of the unit disc and in particular on the unit circle. Due to classical and recent results on the boundary behaviour of Taylor series, for functions in Hardy spaces and Bergman spaces the situation is essentially different. In this paper it is shown that in many respects these results are sharp in the sense that universality generically appears on maximal exceptional sets. As a main to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 19 publications
(26 reference statements)
1
19
0
Order By: Relevance
“…In [5] it is shown that for open sets with 0 ∈ the Taylor shift T is topologically mixing on H ( ) if and only if each connected component of C ∞ \ meets T. Results concerning topological and metric dynamics of the Taylor shift on Bergman spaces are proved in [6] and [16].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…In [5] it is shown that for open sets with 0 ∈ the Taylor shift T is topologically mixing on H ( ) if and only if each connected component of C ∞ \ meets T. Results concerning topological and metric dynamics of the Taylor shift on Bergman spaces are proved in [6] and [16].…”
Section: Introduction and Main Resultsmentioning
confidence: 99%
“…So, for E = e πiC and for f in the disc algebra the only possible uniform limit function of a subsequence of (S n (f, ·)) is the function f | E and thus, in particular, A U uE = ∅. In contrast, as already mentioned in Remark 2.6, Theorem 1.1 in [5] shows that the sequence T n : H 2 → C(E) is hereditarily densely universal for E. Corollary 3.10. Let E = e iA with A ⊂ (−π, π) compact.…”
Section: Theorem 32 the Set A Ku Is Residual In K(t)mentioning
confidence: 93%
“…For m ∈ I we have e 2πiβm/β k = 1 for all k ≤ m and and thus z βm → 1 uniformly on E as m → ∞, m ∈ I.) From Theorem 1.7 and Remark 1.8 in [5] it follows that for each Dirichlet set E there exist power series having the property that (S n (ζ)) is (C, 1)-summable at all points ζ ∈ E (actually on an arc containing E) and so that {S n | E : n ∈ N 0 } is dense in C(E). Up to now, no concrete infinite set E with A U uE = ∅ is known.…”
Section: Theorem 32 the Set A Ku Is Residual In K(t)mentioning
confidence: 94%
See 1 more Smart Citation
“…On other hand, recent results in [2] show that, for any compact subset E ⊆ T of arc length measure 0, the set of all f ∈ H p (D), p ∈ [1, ∞), with the property…”
Section: Introductionmentioning
confidence: 99%